The Holy Spirit and Ecclesiological Political Theology: Erik Peterson and Yves Congar - Grassi, Martín (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2022)
In this paper, I will argue that a Christian Political Theology is mostly to be found in the concepts of the Church and in the performance of the Holy Spirit by examining the works of Erik Peterson and Yves Congar. For both theologians, the political dimension of ecclesiology is grounded on the action of the Holy Spirit, especially considering the birth of the Church in Pentecost, and the pneumatological nature of the sacraments. Although Political Theology focused mainly on the persons of the Father and the Son, I aim at showing how a Christian Political Theology is ultimately grounded on the conceptual transferences between the political and the theological that the Holy Spirit makes possible through the Church: if there is a Christian Political Theology, it is essentially ecclesiological and pneumatological.